Increasing Employee Productivity As The Implementation Of Muslim Work Ethos - Darmawati Darmawati; Luthfi Parinduri (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
Employee productivity is one of the key factors determining the success of an organization. In Islam, good work ethics are not only based on technical competencies and skills but also on moral and spiritual values that improve work quality. The five key elements of Muslim work ethos—sincerity for Allah, honesty in all matters, responsibility toward work and trust, justice in actions, and dedication and professionalism in work—play a significant role in enhancing employee productivity. This article aims to examine the implementation of these five elements of Muslim work ethos across various industry sectors and their impact on employee productivity. Based on literature review, the application of Muslim work ethics has proven to yield significant results in improving productivity, efficiency, and employee satisfaction. This research is expected to contribute to the development of human resource management based on Islamic principles in the workplace.